SOLUBILITIES OF STRONTIUM CARBONATE AND SULFATE IN SEAWATER - Savenko A.V. (My University, 2004)
The solubilities of strontium carbonate and sulfate in weak solutions and seawater were experimentally studieki at 25°C. The thermodynamic solubility products of SrCO3 and SrSO4 in aqueous solutions are estimated at 3.54 × 10-10 and 2.15 × 10-7 and the dissociation constants of SrCO30 and SrSO40 complexes, at 1.86 × 104 and 111. The concentration solubility products of SrCO3 and SrSO4 in aqueous solutions are equal to 9.53 × 10-8 and 1.20 × 10-5. The respective strontium concentrations in seawater with a salinity of 35??? are 600 and 420 μM in equilibrium with these salts. The experimental data were used to calculate the integral activity coefficient of Sr 2+ in seawater (0.170) and proportion of free Sr 2+ ions (76%).